2020
DOI: 10.1155/2020/9659640
|View full text |Cite
|
Sign up to set email alerts
|

Soil Contamination with Toxocara Eggs in Public Schools in Rural Areas of Southern Thailand

Abstract: Soil is considered the primary source of Toxocara transmission to humans, especially children. The status of soil contamination with Toxocara eggs in southern Thailand is unknown. This study aimed at estimating the soil contamination with Toxocara eggs in public schools in Nakhon Si Thammarat province in southern Thailand. Soil samples were collected from 12 public schools between August and September 2017. At each site, ten soil samples were collected from the following five types of locations: (1) playground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
2
5
1
Order By: Relevance
“…Humans acquire T. canis by accidentally ingesting infected eggs, which can be found in several public places [ 35 ]. A previous study conducted in rural areas of southern Thailand reported that the soil samples from public schools were contaminated with Toxocara eggs, especially that in the playgrounds; this correlated with our results as all dog owners reportedly allowed the dog to excrete outside the house (100%) [ 34 ]. This study suggests that people might be infected with T. canis in ways other than by caring for dogs and emphasizes the necessity of hand hygiene to prevent parasite eggs from entering the human body via the fecal–oral route.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Humans acquire T. canis by accidentally ingesting infected eggs, which can be found in several public places [ 35 ]. A previous study conducted in rural areas of southern Thailand reported that the soil samples from public schools were contaminated with Toxocara eggs, especially that in the playgrounds; this correlated with our results as all dog owners reportedly allowed the dog to excrete outside the house (100%) [ 34 ]. This study suggests that people might be infected with T. canis in ways other than by caring for dogs and emphasizes the necessity of hand hygiene to prevent parasite eggs from entering the human body via the fecal–oral route.…”
Section: Discussionsupporting
confidence: 90%
“…This trend has also been reported in previous studies [ 31 , 32 ]. It has been hypothesized that males engage in more outdoor activities than females and, therefore, are more likely to be in contact with contaminated soil and dogs [ 33 , 34 ]. However, univariate and multivariate analyses demonstrated that sex was not significantly associated with seropositivity for anti- T.canis IgG antibodies in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Soil is considered the primary source of Toxocara spp. transmission to humans, especially children [14]. Soil contamination by eggs of Toxocara spp.…”
Section: Discussionmentioning
confidence: 99%
“…Soil is considered the primary source of Toxocara transmission to humans, especially children [14]. Soil contamination by eggs of Toxocara spp.…”
Section: Discussionmentioning
confidence: 99%